ANALYSIS OF WORK AND OPERATION OF ROTOR-TILTING DRUM-TYPE FURNACE - E. A. Kononovich; N. F. Nevar (Литьë и металлургия)
Analysis of works is carried out and characteristics of operation of a rotor-tilting drum-type furnace are given. Technological process of melting of black and nonferrous alloys in a rotor-tilting furnace is considered.